A Pragmatic Analysis of Responses in Malaysian Parliamentary Discourse - Zainal Abidin, Najah; Mohd Jan, Jariah (Journal of Pragmatics Research, 2022)
This study employs the framework of responses proposed by Harris (1991), the notion of implicature as defined by Thomas (1995), and the dimensions of resistance introduced by Clayman (2001) to examine the types of responses in Malaysian Parliamentary Question Time. Analysis revealed the tendency of using direct, indirect, and evasive responses to specific questions for various reasons. Direct answers were observed in questions that could reflect positively on the government’s image. On the contrary, indirect answers were employed in questions that suggest clashing of goals between responders and questioners that could subsequently threaten the image of the government whereas negative presuppositions and the way questions are structured in parliament influence the production of evasion.Keywords: direct answer, evasive response, indirect answer, parliamentary discourse, political discourse